ANALISIS YURIDIS PUTUSAN TATA USAHA NEGARA NOMOR 35/G/2018/PTUN-KPG MENGENAI UPAYA ADMINISTRATIF TERHADAP PEMBERHENTIAN PEGAWAI NEGERI SIPIL SECARA TIDAK HORMAT - Brylianda Robby Prasetyo Hartono; Gandes Candra Kirana (Reformasi Hukum Trisakti, 2021)
Chrisanto Enggong S.Pi, a former civil servant who is the plaintiff, was issued a Decree by the East Manggarai Regent Number BKPSDM.888/1493/XII/2018 concerning Dismissal for Committing a Crime in Position Crime by the defendant and rehabilitate and/or restore the plaintiff's position to its prior state. The issue's formulation is whether State Administrative Decision Number 35/G/2018/PTUN-KPG is in compliance with the applicable statutory regulations and how administrative efforts for civil servants against dishonorable dismissal based on Law Number 5 of 2014 concerning State Civil Apparatus are being carried out. Typical legal research techniques include secondary data collection, descriptive and analytical analysis, library research, and the use of deductive reasoning to reach conclusions. Considering the findings of the study, Discussion and conclusion: The panel of judges is thought to be less impartial in deciding the case when a civil servant who has been dishonorably discharged for this reason submits administrative efforts. All administrative efforts must be made before filing a lawsuit in court.